PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL PROBLEM SOLVING DI SMP PLUS AL MALIKI BOJONEGORO - Hidayah, Asih; Zainudin, Muhammad (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Abstract The purpose of this study is to determine the application of problem solving learning models can improve student learning outcomes in solving mathematical problems of class VIII AL-MALIKI PLUS SMP Bojonegoro. The type of research used is Classroom Action Research. Data collection is carried out by tests, interviews, field notes, and observations. The study was conducted in class VIII A with a total of 20 students with material systems of two variable linear equations. Student learning outcomes increased from cycle I to cycle II which was 70% to 80%. Based on the results of the study it is known that the application of the problem solving learning model can improve the learning outcomes of class VIII AL-MALIKI PLUS SMP Bojonegoro. Keywords: Learning Outcomes, Problem Solving, Mathematical Learning, Problem Solving